Value Co-creation of Food Bank and Stakeholder to Achieve Sustainable NGOs: Agenda for Future Research - Shofiyyah, Yasmin; Novani, Santi (Research Synergy Foundation, 2023)
Food banks appear to be a socially desirable solution to better utilizing food waste from the standpoint of waste reduction since it provides a “win-win” solution. Despite having a valuable mission, sadly, food bank faces several barriers due to their reliance on donations. As a result, collaboration is becoming a desirable step for food banks to increase resources which lead to corporate sustainability. This paper employs a systematic literature review approach to analyze 26 “Food Bank and Stakeholder Partnerships” papers published in the Scopus database over the past five years. The findings indicate that most of research comes from US which have a sustain system of food bank. Numerous studies have examined the collaboration between food banks and different institutions, including healthcare, community, retail, academic, self-organizing, and multi-stakeholder entities which each collaboration gain a uniqueness objective of partnership. This paper discussed the existing of stakeholders and food bank partnership with Four-Co-phase Models of Value Co-creation Process to better understand the phases and traits of partnerships. Communication become an important point on build a sustain partnership. Based on the findings, the topic of communication is widely addressed in articles on collaborative efforts, necessitating further research on trust within collaboration. Further research is needed to explore the sustainability of food banks in developing countries due to limited existing studies. In addition to external collaboration, internal collaboration within the food bank is also important for ensuring organizational harmony in the future.